2015
DOI: 10.1556/004.2015.031
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii antibody dynamics in heifers born to vaccinated versus non-vaccinated dams in a chronically infected dairy herd

Abstract: This study was designed to compare Coxiella burnetii antibody dynamics in heifers born to vaccinated or non-vaccinated dams in a single high-producing dairy herd chronically infected with the bacterium. Antibody dynamics were examined from birth to the postpartum period in replacement heifers (n = 14) born to non-vaccinated dams (n = 7) or to dams that had been vaccinated on gestation days 171-177 (n = 7) and 192-198. Samples of blood, milk, faeces, vaginal fluid, colostrum and cotyledons (the latter two only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…All heifers were seronegative at the age of 9 months as well as 3 weeks before the expected calving date. Tutusaus, Garcia‐Ispierto, and López‐Gatius () demonstrated that maternal antibodies against C. burnetii can be detected until the age of 3 months in dairy calves born in endemically infected herds. Since the age of 6 months, replacement heifers remained seronegative until day 22–28 of the first post‐partum period.…”
Section: Discussionmentioning
confidence: 99%
“…All heifers were seronegative at the age of 9 months as well as 3 weeks before the expected calving date. Tutusaus, Garcia‐Ispierto, and López‐Gatius () demonstrated that maternal antibodies against C. burnetii can be detected until the age of 3 months in dairy calves born in endemically infected herds. Since the age of 6 months, replacement heifers remained seronegative until day 22–28 of the first post‐partum period.…”
Section: Discussionmentioning
confidence: 99%